2013
DOI: 10.5152/tjbh.2013.07
|View full text |Cite
|
Sign up to set email alerts
|

A Challenging Entity in the Differential Diagnosis of Breast Cancer: A Retrospective Analysis of 17 Cases With Granulomatous Lobular Mastitis

Abstract: Results: All the cases were women of childbearing age, who had given birth and breastfed at least once. The most common causes for admission were; breast mass in 12 patients (70.6%) and pain in 12 (70.6%) cases. Five (29.4%) cases developed a fistula and four (23.5%) had abscess requiring drainage. Mammography was used for 10 (58.8%) cases, 12 (70.6%) were examined by MRI and all the patients were evaluated with ultrasound. Five (29.4%) cases were suspicious for malignancy prior to biopsies. Diagnoses of sixte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…On the contrary, Western countries like the USA [15], the UK [5], and New Zeeland [20] have a remarkably lower rate of IGM. Our work, as well as that of others [20,28,29], revealed that IGM is usually seen in women who are lactating or those who have been lactating. This finding may explain why IGM is more common in Middle Eastern countries such as Iran, Turkey, and Egypt than in other regions of the world.…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary, Western countries like the USA [15], the UK [5], and New Zeeland [20] have a remarkably lower rate of IGM. Our work, as well as that of others [20,28,29], revealed that IGM is usually seen in women who are lactating or those who have been lactating. This finding may explain why IGM is more common in Middle Eastern countries such as Iran, Turkey, and Egypt than in other regions of the world.…”
Section: Discussionsupporting
confidence: 81%